PEMANFAATAN HUTAN BAKAU MENJADI DESTINASI EKOWISATA MANGROVE DI KAMPUNG TUA BAKAU SERIP KELURAHAN SAMBAU, KECAMATAN NONGSA, KOTA BATAM - Gatot Morwanto; Depri; Yuanita FD Sidabutar; Ismael P Sinaga (Jurnal Potensi, 2023)
The potential of the Mangrove Forest ecosystem to become an ecotourism attraction for the community's awareness and love for Mangrove Forests is also small. Mangrove ecotourism is located in the Old Mangrove Village of Serip, Nongsa District, Sambau Village. This coastal area has great tourism potential, especially ecotourism potential in the form of beaches or mangrove ecosystems. The use of mangrove forests to become ecotourism is in line with the shift in tourist interest from old tourism to new tourism. Determining the development strategy for Mangrove Forest ecotourism. The type of research used is Data Analysis research, namely SWOT analysis. Strengths are the strength factors possessed by an organization which include skills, products, and so on to achieve organizational goals. Weaknesses that exist within an organization such as limitations in terms of resources, skills, and abilities are serious obstacles to the appearance of satisfactory organizational performance. Opportunities are some favorable environmental situations for a company. Meanwhile, threats are unfavorable environmental factors. Internal and external factors greatly influence the development of mangrove forest sustainability and the development of mangrove ecotourism. Based on the analysis that has been carried out to identify strengths, weaknesses, opportunities, and threats, it can be seen that there are more strengths and opportunities. The development of mangrove forest ecotourism has the opportunity to take advantage of the power to develop ecotourism in the Kampung Tua Bakau Serip area, namely to be able to create new jobs, especially in the field of tourism, especially for local communities. other tourism communities that take advantage of the available potential. Utilizing available attractions and adding supporting attractions, empowering local communities, and utilizing locations to become tourism businesses.